Study on Sports, Extracurricular Activities, Electronic Device Usage Factors Associated with Chronic Fatigue Syndrome in Taiwanese Preschoolers - Su-Fen Huang; Hui-Ying Duan (MDPI AG, 2023)
Under the impact of the pandemic, electronic device usage has become the primary tool for learning. Due to social distancing restrictions, many sports facilities have been forced to close, resulting in changes in daily activities for preschool children. This research aimed to investigate the sports, extracurricular activities, and electronic device usage factors associated with chronic fatigue syndrome among Taiwanese preschoolers. Five-year-old preschoolers were randomly selected using a stratified multi-stage random cluster sampling method. The parents of the preschoolers completed the questionnaires, which contained items related to the symptoms of fatigue, extracurricular activities, and electronic device usage of their preschoolers. A total of 1536 valid questionnaires were returned. The data were then analyzed using descriptive statistics and the chi-square test. The following results were obtained: (1) the preschoolers who exercised at least three times per week, engaged in sweating exercise for at least 30 min at a time, had a continuous rhythmic exercise habit, and participated in a variety of exercise types experienced a lower degree of fatigue; (2) the preschoolers who engaged in extracurricular activities every day exhibited a higher degree of fatigue; (3) the preschoolers who watched television or used smartphones to pass the time due to boredom, watched television or used smartphones on holidays, played video games or surfed the Internet due to boredom, and played video games or surfed the Internet on holidays displayed a higher degree of fatigue. This research verified that regular exercise with various sports, extreme extracurricular activities, and laissez-faire electronic device usage are factors associated with fatigue syndrome in preschoolers. It is suggested to develop children's regular exercise habits, avoid excessive extracurricular activities, and guide their electronic device usage.